Predictors of response and long-term tolerability of sparsentan in a real-world IgA nephropathy cohort - Anila Cara; Maria J Vargas-Brochero; Cristián Juanet; Gian Marco Berti; Ilario Russo; Fernando C Fervenza; Ladan Zand (Clinical Kidney Journal, 2026)
Abstract Background Sparsentan, a dual endothelin type A and angiotensin II type 1 receptor antagonist (DEARA), has demonstrated antiproteinuric efficacy in randomized trials of IgA nephropathy (IgAN). However, real-world data on treatment response and predictors remain limited. We evaluated longitudinal proteinuria response, kidney function trajectories, and predictors of treatment response over the first year of sparsentan therapy in routine practice. Methods In this single-center observational study, 38 adults with biopsy-proven IgAN were evaluated at baseline, 3, 6, 9, and 12 months after sparsentan initiation. Predictors of response, defined as ≥ 50% proteinuria reduction with ≤ 15% decline in estimated glomerular filtration rate (eGFR), were evaluated at the 9-month landmark analysis using logistic regression. Longitudinal proteinuria and eGFR trajectories were analyzed using linear mixed models. Results Sparsentan was associated with sustained proteinuria reduction across patient subgroups. In mixed-effects models, proteinuria declined by approximately 8% per month, while the annualized eGFR slope was − 2.5 mL/min/1.73 m²/year. At the 9-month landmark analysis, baseline hematuria (OR 10.00; 95% CI 1.28–78.12; P = 0.028) and higher systolic blood pressure (sBP) (OR 4.30; 95% CI 1.02–18.10; P = 0.047) were associated with higher odds of response. Sparsentan was generally well tolerated, with discontinuation in 10.5% of patients, including two cases of reversible liver enzyme elevation. Conclusion In routine practice, sparsentan was associated with sustained antiproteinuric effects with relatively stable kidney function trajectories despite advanced baseline disease. Exploratory analysis identified baseline hematuria and sBP as potential markers of treatment response; however, these findings require validation in larger prospective cohorts.